2004
DOI: 10.3168/jds.s0022-0302(04)73275-0
|View full text |Cite
|
Sign up to set email alerts
|

Relative Acidifying Activity of Anionic Salts Commonly Used to Prevent Milk Fever

Abstract: High cation diets can cause milk fever in dairy cows as they induce a metabolic alkalosis reducing the ability of the cow to maintain calcium homeostasis at the onset of lactation. Adding anions to the diet can offset the effect of the high cation forages by inducing a mild metabolic acidosis, restoring the ability to maintain calcium homeostasis. The difference in mEq of dietary cations and anions (DCAD) is most often expressed as (Na(+) + K+) - (Cl- + S(--)). This equation implies that a mEq of chloride and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
52
0
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(64 citation statements)
references
References 17 publications
(23 reference statements)
8
52
0
3
Order By: Relevance
“…The decrease of urine pH after application of sulphate was observed in studies of Goff et al (2004), Peterson et al (2005) and Chan et al (2006). Chiappi (2003) suggested, that application of the high amount of calcium (100 g of Ca) could limit anions acidifying effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The decrease of urine pH after application of sulphate was observed in studies of Goff et al (2004), Peterson et al (2005) and Chan et al (2006). Chiappi (2003) suggested, that application of the high amount of calcium (100 g of Ca) could limit anions acidifying effect.…”
Section: Discussionmentioning
confidence: 99%
“…with the large amount of dietary Ca and have a negative effect on the process of ovulation. Goff et al (2004) suggested that hydrated magnesium sulphate could be used not only as acidifying agent, but also as a source of magnesium. Among the anion salts, this compound has the least effect in decreasing appetite in cows (Goff 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Equation D can serve the same purpose (Goff et al, 1991). The last equation J, (Na + K) − (Cl + 0,6S), was the most recently proposed by Goff et al (2004).…”
Section: Anionic Dietmentioning
confidence: 99%
“…(ii) Milk fever: The feeding of a diet high in cations especially in K and Na in dry period tends to increase incidence of milk fever (Goff et al,2004). Whereas, feeding cows with diet relatively high in anion, primarily Cl and SO 4 may help to prevent milk fever.…”
Section: Feeding For Immunity To Infectious Disease (I) Mineralsmentioning
confidence: 99%